Features of Philosophical Problems in Social Sciences and Humanities - Axmedov Abdulxay Toshto'xtaevich (International Journal on Economics, Finance and Sustainable Development, 2021)
This article discusses the philosophical problems of the social sciences and humanities. In the article, the author analyzes the role of social sciences and humanities in the development of society